DINAMIKA ESTETIK TARI TOPENG KLANA GANDRUNG: TRANSFORMASI GAYA MIMI RASINAH SEBAGAI UPAYA REGENERASI - Nanan Supriyatna; Farah Nurul Azizah (Greget: Jurnal Kreativitas dan Studi Tari, 2026)
The Klana Gandrung Mask Dance is an integral part of the Indramayu Mask Dance repertoire, which persists today due to the role of dalang topeng as cultural agents. In the context of Indramayu Mask Dance, Mimi Rasinah, a maestro of the Pekandangan style, has had a fundamental influence on the characteristics of this dance. Currently, the artistic mantle has been passed down to her granddaughter, Aerli, as a strategic step in maintaining the continuity of the tradition. Despite being within the same lineage, there are choreographic discrepancies in the Klana Gandrung Mask Dance between the eras of Mimi Rasinah and Aerli. This phenomenon indicates an aesthetic transformation influenced by the dancer's personal style and adaptation to contemporary demands within its supporting environment. This study aims to analyze the transformation of the Klana Gandrung dance structure, which characterizes each dancer, while documenting the efforts toward artistic regeneration in Indramayu. The findings are expected to contribute to the development of arts teaching materials, choreographic innovation, and cultural archiving. This research employs a qualitative method with an ethnographic approach. Data were collected through field observations in Pekandangan, in-depth interviews, and documentation studies. The analysis of choreographic structural transformation is examined through Anthony Giddens’ Structuration Theory, focusing on the agent's actions in modifying pre-existing dance structures. Additionally, Laban Movement Analysis (LMA) is utilized as a technical analytical tool to identify detailed changes in movement forms across the two generations of dancers. The research findings suggest that the heir's creative treatment represents a negotiation between tradition and contemporary stage demands, ultimately enriching the aesthetic treasury of the Pekandangan Mask Dance.